(untitled) (Minerva, 2018)
Galen is probably the Greek author who transmits more information about the genesis of his own works, the fixation of the text, its distribution and finally its publication. The study that we now present, has as its object the reading, translation and annotation of the passages of Galen’s work in which the Greek terms ἔκδοσις (ékdosis) and ἐκδίδωμι-προεκδίδωμι (ekdídōmi-proekdídōmi) appear within the works of Galen.